THE ROLE OF MARKETING MIX (7 P'S) TOWARDS REPURCHASE INTENTION OF ALIBABA'S FRIED BANANA IN BANDUNG CITY - Marceilla Suryana; Sarfilianty Anggiani (Program Studi Magister Manajemen, 2023)
This study aims to find out the impact of the marketing mix (7 p's) on the repurchase intension of Alibaba Bandung's Pisang Goreng. The research method used in this study is a quantitative descriptive approach. The sampling technique used is the slovin formula, that obtained by giving out the questionnaire to 98 respondents. This study used qualitative data and multiple regression analysis as the analysis methods. All variable indicators are declared valid and reliable. The result of the F-test proves that the product, price, place, promotion, people, physical evidence, and proser variable simultaneously has an impact on the repurchase intension of Alibaba Bandung's Pisang Goreng. The result of the t-test proves that product and promotion have an impact on the repurchase intension of Alibaba Bandung's Pisang Goreng.